Gestión directiva y clima organizacional en la educación de personas adultas en Chile - Sagredo Lillo, Emilio; Castelló Tarrida, Antoni (Universidad de Costa Rica, 2019)
The organizational environment perceived in educational contexts and the management developed to contribute to the institutional environment are key to the development of the learning-teaching process. This topic has been investigated in education, but no evidence of this has been found in education for young people and adults, a population that is relevant to the social and economic development of the country.The objectives of this research are to know the correlation that could exist among directive management, motivation and teachers’ commitment in adult educational institutions from the Biobío region, Chile. A selective or correlational methodology was used, its design is non-experimental, transversal and intrasubject. It worked with a hypothesis of association or covariation, therefore, the relationship between variables is sought. The population of this research is made up of teachers who work in Adult Education Centers of the Biobío Region of Chile, the sample consists of 40 Teachers from educational institutions from the Communes of Los Angeles and Concepción. A Likert scale survey was used as a data collection instrument. It was worked with the Spearman correlation for its analysis, because the sample does not meet normality criteria. The results show that in the perception of teachers who work in the educational level studied, that there is a positive and significant correlation between directive management, teacher motivation and commitment likewise, a positive and significant correlation was found between teacher motivation and commitment.